From Ann Brown to Deanna Kuhn: a tale of two research perspectives on learning. Issue 2 (2nd July 2016) - Jan, Mingfong
ABSTRACT: This paper examines two research perspectives on learning – developmental psychology and the learning sciences. We compare and contrast works from two leading researchers – Deanna Kuhn and Ann Brown – as a way to illustrate how questions and research on learning, such as problem-solving, inquiry, metacognition, self-directed learning, are raised and answered. The developmental psychology perspectives, represented by Deanna Kuhn, often highlight individual attributes, foregrounding deep understanding of what is in the head. The learning sciences perspectives, manifested by Ann Brown, inquire learning taking place within the material, social, and cultural contexts, foregrounding the design of what the head is in. The former takes an observer-evaluator-theorizer position to understand how learning develops over time. The later takes an ethnographer-designer-interventionist-theorizer position to understand how individual and group learning can be changed via design. This paper contributes to the delineation of two leading ways to understand how people learn. It informs researchers how research tool kits are shaped when their research commitments differ.